Soil structure interaction effects on strength reduction factors - Eser, Muberra; Aydemir, Cem; Ekiz, Ibrahim (TECHNO-PRESS, 2012)
In this study, strength reduction factors are investigated for SDOF systems with period range of 0.1-3.0 s with elastoplastic behavior considering soil structure interaction for 64 different earthquake motions recorded on different site conditions such as rock, stiff soil, soft soil and very soft soil. Soil structure interacting systems are modeled and analyzed with effective period, effective damping and effective ductility values differing from fixed-base case. For inelastic time history analyses, Newmark method for step by step time integration was adapted in an in-house computer program. Results are compared with those calculated for fixed-base case. A new equation is proposed for strength reduction factor of interacting system as a function of structural period of system (T), ductility ratio (mu) and period lengthening ratio (T/T). It is concluded that soil structure interaction reduces the strength reduction factors for soft soils, therefore, using the fixed-base strength reduction factors for interacting systems lead to non-conservative design forces.
Keywords: soil-structure interaction; strength reduction factors; ductility demand; structural analysis; Engineering